Study the Effect of Corrosion on the Pipes of Oil Well Production - Hamied, Ramzy. S.; Alhassan, Mohammad. A.; Al-Bidry, Mayssaa. A. (Journal of Petroleum Research and Studies, 2018)
Corrosion costs of the oil industry are billions of dollars in a year. Corrosion affects every aspect of exploration and production of oil, from offshore rigs to casing and transporting the crude oil to refinery or exporting terminal. This study aims to investigate the effect of sulfur content on the corrosion of carbon steel and composite material (polyester/fiberglass) pipes used in well production. . In the present work three specimens of pipes from (Al – Nasiriyah oil field, Al – Daura refinery, and composite material) are prepared in the center of the training and workshop in university of technology with (3, and 5 mm) thickness and (30 mm) diameter which immersed in different types of Iraqi crude oil field (East – Baghdad, Al – Nasiriyah, and Al – Rumaila field) in different times (0, 14, 28, 42, and 56 day). Physical properties (viscosity, density, API grade, specific gravity (sp.gr), sulfur %, sediment %, and water %) of three types of Iraqi crude oil are tested in lab of petroleum technology department. Also study specimens of pipes by microscope to knowing the effect of sulfur % on these specimens. . The results showed that when increasing duration of immersed pipes and sulfur content in crude oil increased the rate of corrosion, and the composite material pipe gives the best result compared with the other two specimens pipes used because they didn’t influenced by corrosion when immersed in Iraqi crude oil. Also, it was noted that the diffusion coefficient decreased in composite pipe compared with the other pipes.